Design of Cockle’s Meat Separator Machine Using Cost Based Design Method - Hassan Nusi, Muhamad Afiq; Muhd Nor, Nik Hisyamudin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Cockle is one of the seafood that Malaysian people love to eat and from this news, it shows that cockle industry is important in Malaysia because of the high demand. The lack of technologies in this industry have made the production of the industry been limited and cannot meet the demand that will be needed. This study is to design the machine to separate the meat of the cockle from it shell in automatic to enhance the production of the industry. The design is simple where there are two stages to separate the meat by using the crushing method and the next stage is by using the vibration screening to separate the meat from the shell. The design and simulation of the machine has been carried out using a SolidWorks application. The machine that has been design will help the small business company to growth by using the affordable machine in producing the meat that have been separate.